Utilisation of fly ash and sewage sludge ash based geopolymer with cement for the production of compressed stabilized earthen block - Tisha Sikder; Shantanu Paul; Mohammad Shariful Islam (European Journal of Environmental and Civil Engineering, 2026)

Green gold for global health: Unlocking the nutritional and therapeutic power of bamboo - Mrinmoy Kundu; Liza Farzana; Md. Al Emran Hosen; Shariful Islam; Monisha Akter Rupa; Md. Rasel Mia; Jamial Hashin Himel; Md. Motaher Hossain (Food and Humanity, 2026)

Nutritional potentials of underutilized marine fish species from the Bay of Bengal: A sustainable path to future food solutions - Suprakash Chakma; Md. Alamgir Kabir; Srijita Howlader; Md. Arifur Rahman; Newton Saha; Tania Tabassum; Sohel Rana Jony; Md. Shariful Islam; Md. Isfatuzzaman Bhuyan; Md. Sazedul Hoque (Food and Humanity, 2026)

Spatio-temporal distribution patterns and risk assessment of microplastics along a coastal beach in southern Bangladesh - Md. Shawon Hossain; Kowshik Das Karmaker; Mahfujur Rahman; Arnob Ghosh; Swachsa Rahman; Shamiha Shafinaz Shreya; Jarin Tasnim; Mahir Tajwar; Nusrat Jahan Shimu; Mahmud Al Noor Tushar; Mir Shariful Islam; Mohammad Abdul Momin Siddique; et al. (Marine Pollution Bulletin, 2026)

Distribution, source, and risk analysis of PAHs and trace elements in roadside soils of Dhaka-Bhanga expressway: a case study - S. M. Fazle Rabbi; Lamyea Rahman; Md. Samrat Mohay Menul Islam; Md. Ashraful Islam; Shariful Islam; Md. Mashfiqur Rahman Niloy; Muhammad Abu Bakar; Md. Rakibul Hasan; Md. Kamruzzaman (Environmental Monitoring and Assessment, 2026)

Marine invertebrates as ecological integrators of microplastic pollution: Trait-based evidence from coastal Bangladesh - Swachsa Rahman; Saikat Das; Abdullah Yebna Ahammad; Arnob Ghosh; Md. Mushfiqur Rahman; Md. Biplob Hasan; Mahmudul Hasan; Goutam Kumar Kundu; Mir Shariful Islam; Md. Habibullah-Al-Mamun (Regional Studies in Marine Science, 2026)

From water and sediment to seafood: Heavy metal contamination and human health risk in wild and cultured oysters from a developing coastal region - Mahima Ranjan Acharjee; Subeda Newase; Sadia Afrin; Shariqul Islam; Md. Abdullah Al Mamun Hridoy; Mohammad Ekramul Haque; Trina Das; Sifatun Nur; Helena Khatoon; Tashrif Mahmud Minhaz; Yeasmin Nahar Jolly; Mohammed Shariful Azam; et al. (Marine Pollution Bulletin, 2026)

From ocean to table: marine contaminants and their risks to human health and biodiversity - Mohammad Nazrul Islam Bhuiyan; Md. Saidur Rahman; Md. Mahfuzur Rahman; Shariful Islam; Priyanka Dey Suchi; Barun Kanti Saha (Marine Pollution Bulletin, 2026)

Species-specific bioaccumulation of toxic metals in coastal seaweeds from the northeast Bay of Bengal: Implications for human health risk - Md. Biplob Hasan; Md. Mushfiqur Rahman; Arnob Ghosh; Swachsa Rahman; Mahmudul Hasan; Md. Habibullah-Al-Mamun; Mir Shariful Islam (Regional Studies in Marine Science, 2026)

Load–Transfer Model Calibration for Pile Foundations in Deltaic Soil Profiles - Mohammad Shahidul Islam; Saidis Salekin Aninda; Mohammad Shariful Islam; Mohammed Kabirul Islam (Geotechnical and Geological Engineering, 2026)

Marine algae from coastal Bangladesh: Insights into nutritional potential and dietary implications - Swachsa Rahman; Md. Zia Uddin Al Mamun; Fateeha Noor; Mir Shariful Islam; Moniruzzaman Khondker; Mahmudul Hasan; Md. Tazinur Rahman; Mustafizur Rahman Naim (Regional Studies in Marine Science, 2026)

Comparative assessment of nutritional quality and ecotoxicological biomarkers in Paphia textile clams from the coastal areas in Egypt - Amel H. El-Gendy; Md. Mushfiqur Rahman; Arnob Ghosh; Mir Shariful Islam; Abdullah A. Alkahtane; Saleh Al Farraj; Md. Habibullah-Al-Mamun (Regional Studies in Marine Science, 2025)

Prediction and optimization of efficient ship design particulars through advanced machine learning approaches - S.M. Rashidul Hasan; Md Shariful Islam; Zobair Ibn Awal; Khandakar Akhter Hossain (Ocean Engineering, 2025)

Advancing mass seed production of mud crab (Scylla olivacea) in captive conditions: challenges and opportunities for sustainable aquaculture development in Bangladesh - Zobaer Masum; Mohammad Abu Naeem; Syduzzaman; Md. Rakeb-Ul Islam; Md Asaduzzaman; Mohammed Shariful Azam; Benoy Kumar Barman; Abdullah-Al Mamun (Aquaculture International, 2025)

Experimental and numerical investigation of the compressive properties of nanoclay reinforced honeycomb structures - Taslim Ben Alam Protik; Md Shariful Islam; Md Arifuzzaman; Md Abdullah Al Bari (Next Research, 2025)

Influence of Rainfall Infiltration and Hydraulic Conductivity on Hillslope Stability - Ajoy Paul; Mohammad Shariful Islam; Apiniti Jotisankasa; Samira Tasnim Progga (Geotechnical and Geological Engineering, 2025)

Three-dimensional numerical investigation of ground settlement caused by side-by-side twin tunnels - Md Shariful Islam; Magued Iskander (Tunnelling and Underground Space Technology, 2025)

Particulate matter exposure to street vendors in Dhaka city and associated health risk study - Md. Shariful Islam; Shahid Uz Zaman; Md. Safiqul Islam; Shatabdi Roy; Mahbuba Yesmin; Shih-Chun Candice Lung; Abdus Salam (Air Quality, Atmosphere & Health, 2025)

Exploring the effects of spontaneous and solid-state fermentation on the physicochemical, functional and structural properties of whole wheat flour (Triticum aestivum L.) - Shariful Islam; Md. Abdus Satter Miah; Md. Faridul Islam; Mohammad Nazrul Islam Bhuiyan; Khurshida Jahan Tisa; Mustafizur Rahman Naim (Innovative Food Science & Emerging Technologies, 2024)

Nanocellulose-based porous lightweight materials with flame retardant properties: A review - Shariful Islam Tushar; Habibur Rahman Anik; Md Mazbah Uddin; Sumit Mandal; Vijay Mohakar; Smriti Rai; Suraj Sharma (Carbohydrate Polymers, 2024)

Correction: Effect of Banana Pseudostem Derivative Compost and Foliar Spray of Sap on Nutrient Acquisition, Yield and Sugar Content of Corn in Tropical Soil - Mahammad Shariful Islam; Mst. Fatima Khatun; Md. Khairul Alam; Mohammad Amdadul Haque; M. F. A. Anik; H. M. Khairul Bashar; Akbar Hossain; Susilawati Kasim (Journal of Soil Science and Plant Nutrition, 2024)

Effect of Banana Pseudostem Derivative Compost and Foliar Spray of Sap on Nutrient Acquisition, Yield and Sugar Content of Corn in Tropical Soil - Mahammad Shariful Islam; Mst. Fatima Khatun; Md. Khairul Alam; Mohammad Amdadul Haque; M. F. A. Anik; H. M. Khairul Bashar; Akbar Hossain; Susilawati Kasim (Journal of Soil Science and Plant Nutrition, 2024)

Nutritional composition, bioactive compounds, and pharmacological activities of tossa jute sprout (Corchorus olitorius L.): A potential functional food - Sharmin Akter; Mohammed A. Satter; Khondoker Shahin Ahmed; Sattyajit Biswas; Md Abdul Bari; Avizit Das; Mohammad Ahsanul Karim; Niloy Saha; Hemayet Hossain; Shariful Islam; Khurshida Jahan Tisa; A.M. Swaraz (Food Bioscience, 2024)

Appraising water resources for irrigation and spatial analysis based on fuzzy logic model in the tribal-prone areas of Bangladesh - Md. Shariful Islam; Udoy Jibon Tripura; Md. Saiful Islam; Abu Reza Md. Towfiqul Islam; S. M. Rabbi Al Zihad; Mst. Moriom Khatun; Md. Mahadi Hasan; Tuba Yasmin Lubna (Environmental Monitoring and Assessment, 2024)

Ground settlement caused by perpendicularly crossing twin tunnels, a parametric study - Md Shariful Islam; Magued Iskander (Tunnelling and Underground Space Technology, 2024)

Application of AHP and geospatial technologies to assess ecotourism suitability: A case study of Saint Martin's Island in Bangladesh - Md. Habibur Rahman Habib; Mahfujur Rahman; Md. Mahin Uddin; Nusrat Jahan Shimu; Mahmudul Hasan; Md. Jobaer Alam; Mir Shariful Islam (Regional Studies in Marine Science, 2024)

Long-term properties and microstructural characterization of natural clinoptilolite zeolite-based cementitious materials - M. Shariful Islam; Benjamin J. Mohr (Innovative Infrastructure Solutions, 2023)

Food safety policy enforcement and associated actions reduce lead chromate adulteration in turmeric across Bangladesh - Jenna E. Forsyth; Musa Baker; Syeda Nurunnahar; Shariful Islam; M. Saiful Islam; Tauhidul Islam; Erica Plambeck; Peter J. Winch; Dinsha Mistree; Stephen P. Luby; Mahbubur Rahman (Environmental Research, 2023)

Creep Response of Untreated and Additive Treated Jute Geotextiles in Isothermal Condition - Shafiqul Islam; Mohammad Shariful Islam; Tausif E. Elahi; Abdul Jabbar Khan (Geotechnical and Geological Engineering, 2023)

Longitudinal settlements during tunneling in soft Clay, using transparent soil models - Abdelaziz Ads; Md Shariful Islam; Magued Iskander (Tunnelling and Underground Space Technology, 2023)

Endosulfan affects embryonic development synergistically under elevated ambient temperature - Tanjeena Zaman; Talukdar Mohammad Fahad; Masud Rana; Md Shahadat Hossain; Al Mamun; Md Anwarul Haque; Ashananda Sarker; Md Shariful Islam; Md Minhaz-U. L. Haque; Tarannum Naz; Md Imran Nur Manik; Hazrat Ali; et al. (Environmental Science and Pollution Research, 2023)

Three-dimensional numerical investigation of ground settlement caused by piggyback twin tunnels - Md Shariful Islam; Magued Iskander (Tunnelling and Underground Space Technology, 2023)

Serological evidence of bluetongue virus and associated factors in small ruminants of Bangladesh - Shariful Islam; Md Kaisar Rahman; Josefina Abedin; Shafayat Zamil; Md Abu Sayeed; Mohammed Ziaur Rahman; Ariful Islam (Preventive Veterinary Medicine, 2023)

Epidemiology of Group A rotavirus in rodents and shrews in Bangladesh - Ariful Islam; Mohammad Enayet Hossain; Ausraful Islam; Shariful Islam; Md. Kaisar Rahman; Rashedul Hasan; Mojnu Miah; Mohammed Ziaur Rahman (Veterinary Research Communications, 2023)
Rodents and shrews live in close proximity to humans and have been identified as important hosts of zoonotic pathogens. This study aimed to detect Group A rotavirus (RVA) and its potential risk factors in rodents and shrews in Bangladesh. We captured 417 small mammals from 10 districts with a high degree of contact between people and domestic animals and collected rectal swab samples between June 2011 and October 2013. We tested the swab samples for RVA RNA, targeting the NSP3 gene segment using real-time reverse transcription-polymerase chain reaction (rRT-PCR). Overall, RVA prevalence was the same (6.7%) in both rodents and shrews. We detected RVA RNA in 5.3% of Bandicota bengalensis (4/76; 95% CI: 1.4–12.9), 5.1% of B. indica (4/79; 95% CI: 1.4–12.4), 18.2% of Mus musculus (4/22; 95% CI: 5.2–40.3), 6.7% of Rattus rattus (6/90; 95% CI: 2.5–13.9), and 6.7% of Suncus murinus (10/150; 95% CI: 3.2–11.9). We found significantly more RVA in males (10.4%; OR: 3.4; P = 0.007), animals with a poor body condition score (13.9%; OR: 2.7; P = 0.05), during wet season (8.3%; OR: 4.1; P = 0.032), and in urban land gradients (10.04%; OR: 2.9; P = 0.056). These findings form a basis for understanding the prevalence of rotaviruses circulating among rodents and shrews in this region. We recommend additional molecular studies to ascertain the genotype and zoonotic potential of RVA circulating in rodents and shrews in Bangladesh.

Submergence and Wave Action Resilience of Vetiver Grass Protected Fly Ash Amended Soil Slopes - Tanzila Islam; Mohammad Shariful Islam (Geotechnical and Geological Engineering, 2022)

Mechanical Effect of Vetiver Grass Root for Stabilization of Natural and Terraced Hill Slope - Shamontee Aziz; Mohammad Shariful Islam (Geotechnical and Geological Engineering, 2022)

Effect of Face Losses and Cover-to-Diameter Ratio on Tunneling Induced Settlements in Soft Clay, Using Transparent Soil Models - Abdelaziz Ads; Md Shariful Islam; Magued Iskander (Geotechnical and Geological Engineering, 2021)

Escalating SARS-CoV-2 circulation in environment and tracking waste management in South Asia - Ariful Islam; Md. Abul Kalam; Md. Abu Sayeed; Shahanaj Shano; Md. Kaisar Rahman; Shariful Islam; Jinnat Ferdous; Shusmita Dutta Choudhury; Mohammad Mahmudul Hassan (Environmental Science and Pollution Research, 2021)

A simple approach for estimating contribution of vetiver roots in shear strength of a soil–root system - Faria Fahim Badhon; Mohammad Shariful Islam; Md. Azijul Islam; Md. Zia Uddin Arif (Innovative Infrastructure Solutions, 2021)

Infiltration in vegetated soil: empirical modeling and sensitivity analysis - Md. Enayet Chowdhury; Mohammad Shariful Islam; Tahsina Alam; Sagar Barua; Md. Safin Shahriar; Humaira Anisa (Modeling Earth Systems and Environment, 2021)

Experimental Investigation on the Strength and Deformation Aspects of Thixotropic Aging in Reconstituted Clays - Md. Kausar Alam; Azmayeen Rafat Shahriar; Mohammad Shariful Islam; Naveel Islam; Md. Zoynul Abedin (Geotechnical and Geological Engineering, 2021)

Influence of vetiver grass (Chrysopogon zizanioides) on infiltration and erosion control of hill slopes under simulated extreme rainfall condition in Bangladesh - Md Azijul Islam; Mohammad Shariful Islam; Md. Enayet Chowdhury; Faria Fahim Badhon (Arabian Journal of Geosciences, 2021)

Potential of Micranthemum umbrosum for phytofiltration of organic arsenic species from oxic water environment - Md. Shariful Islam; M. Tajuddin Sikder; M. Kurasaki (International Journal of Environmental Science and Technology, 2017)

Effects of Nitrogen, Phosphorous and Potassium on Host-Choice Behavior of Brown Planthopper, Nilaparvata lugens (Stål) on Rice Cultivar - Md Mamunur Rashid; Mahbuba Jahan; Khandakar Shariful Islam (Journal of Insect Behavior, 2017)